The Seasonal and Inter-Annual Fluctuations of Plankton Abundance and Community Structure in a North Atlantic Marine Protected Area - Benedetti, Fabio; Jalabert, Laëtitia; Sourisseau, Marc; Becker, Beatriz; Cailliau, Caroline; Desnos, Corinne; Elineau, Amanda; Irisson, Jean-Olivier; Lombard, Fabien; Picheral, Marc; Stemmann, Lars; Pouline, Patrick (Frontiers in Marine Science, 2019)
Marine Protected Areas have become a major tool for the conservation of marine biodiversity and resources. Yet our understanding of their efficacy is often limited because it is measured for a few biological components, typically top predators or species of commercial interest. To achieve conservation targets, marine protected areas can benefit from ecosystem-based approaches. Within such an approach, documenting the variation of plankton indicators and their covariation with climate is crucial as plankton represent the base of the food webs. With this perspective, we sought to document the variations in the emerging properties of the plankton to better understand the dynamics of the pelagic fishes, mammals and seabirds that inhabit the region. For the first time, we analyze the temporal variations of the entire plankton community of one of the widest European protected areas, the Parc Naturel Marin de la Mer d’Iroise. We used data from several sampling transects carried out in the Iroise Sea from 2011 to 2015 to explore the seasonal and inter-annual variations of phytoplankton and mesozooplankton abundance, composition and size, as well as their covariation with abiotic variables, through multiple multivariate analyses. Overall, our observations are coherent with the plankton dynamics that have been observed in other regions of the North-East Atlantic. We found that both phytoplankton and zooplankton show consistent seasonal patterns in taxonomic composition and size structure but also display inter-annual variations. The spring bloom was associated with a higher contribution of large chain-forming diatoms compared to nanoflagellates, the latter dominating in fall and summer. Dinoflagellates show marked inter-annual variations in their relative contribution. The community composition of phytoplankton has a large impact on the mesozooplankton together with the distance to the coast. The size structure of the mesozooplankton community, examined through the ratio of small to large copepods, also displays marked seasonal patterns. We found that larger copepods (members of the Calanidae) are more abundant in spring than in summer and fall. We propose several hypotheses to explain the observed temporal patterns and we underline their importance for understanding the dynamics of other components of the food-web (such as sardines). Our study is a first step toward the inclusion of the planktonic compartment into the planning of the resources and diversity conservation within the Marine Protected Area.